Supply, installation, testing and commissioning of cctv surveillance system at different units/ projects entry exit points, material stores, explosive magazine, weighbridges and other sensitive places [Tender documents : T29042966] (MENA Report, 2015)
Tender notice number : GM (NK)/EnM/Tender Notice/CCTV/2015-16/014 (c) 2015 Al Bawaba (Albawaba.com) Provided by SyndiGate Media Inc. ( Syndigate.info ).